When global becomes local: Gold Coast 2018 Commonwealth Games international communicable disease surveillance - Kaitlyn Miranda Vette; Patiyan Andersson (University of New South Wales, 2019)
The 21st Commonwealth Games (the Games) was hosted on the Gold Coast, Australia in April 2018. With a large number of international travellers congregating at the mass gathering, it was important to monitor international communicable disease outbreaks with potential to be imported into Australia. The Australian Government Department of Health (DoH) conducted and reported enhanced international communicable disease surveillance during and surrounding the Games period. Surveillance focused on diseases with higher than normal incidence in Commonwealth countries with potential to be imported through travellers and ability to continue transmission in Australia. Over four months, 27 disease events were identified, monitored and reported to local, state and federal public health authorities, as well as general practitioners and pathologists throughout Queensland. Surveillance provided situational awareness for decision making and risk assessment during the Games. It complemented and informed surveillance of local disease activity during the Games and allowed frontline health professionals to contextualise disease presentations.